Higher docosahexaenoic acid levels lower the protective impact of eicosapentaenoic acid on long-term major cardiovascular events - Le, Viet T.; Knight, Stacey; Watrous, Jeramie D.; Najhawan, Mahan; Dao, Khoi; McCubrey, Raymond O.; Bair, Tami L.; Horne, Benjamin D.; May, Heidi T.; Muhlestein, Joseph B.; Nelson, John R.; Carlquist, John F.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Long chain omega-3 polyunsaturated fatty acids (OM3 PUFA) are frequently used for cardiovascular prevention. High dose eicosapentaenoic acid (EPA) is reported to reduce major adverse cardiovascular events (MACE); however combined EPA and docosahexaenoic acid (DHA) preparations have not been shown to reduce MACE. This study sought to assess any interaction between EPA and DHA levels on long-term MACE.Methods: We studied a cohort of 987 randomly selected subjects enrolled in the INSPIRE biobank registry who underwent coronary angiography. We used rapid throughput liquid chromatography-mass spectrometry to quantify plasma levels of EPA and DHA and examined their impact unadjusted, adjusted for one another, fully adjusted for comorbidities, EPA+DHA, and the EPA / DHA ratio, on long-term (10-year) MACE (all-cause death, myocardial infarction, stroke, heart failure hospitalization).Results: Subject age averaged 61.5 ± 12.2 y, 57% were male, 41% were obese, 42% had severe CAD, and 311 (31.5%) had a MACE. The unadjusted hazard ratio (HR) of 10-year MACE for the highest (4 th ) vs lowest (1 st ) quartile (Q) of EPA was HR=0.48 (95% CI: 0.35, 0.67).Adjustment for DHA changed the HR to 0.30 (CI: 0.19, 0.49) and after additional adjustment for baseline differences the HR was 0.36 (CI: 0.22, 0.58). Conversely, unadjusted DHA did not significantly predict MACE, but adjustment for EPA resulted in a 1.81-fold higher MACE risk (CI: 1.14, 2.90) for Q4 versus Q1. However, after adjusting for baseline differences the MACE risk was not significant for DHA (HR=1.37; CI: 0.85, 2.20) An EPA/DHA ratio ≥1 resulted in a lower rate of 10-year MACE outcomes (27% vs 37%, adjusted p-value=0.013).Conclusions: Higher levels of EPA but not DHA are associated with a lower risk of MACE. When combined with EPA, higher DHA blunted the benefit of EPA and was associated with higher MACE risk in the presence of low EPA. These findings can help to explain the discrepant results of EPA-only and mixed EPA plus DHA clinical supplementation trials.